Atypical Creutzfeldt-Jakob Disease Evolution after Electroconvulsive Therapy for Catatonic Depression - Grande, Iria; Fortea, Juan; Gelpi, Ellen; Flamarique, Itziar; Udina, Marc; Blanch, Jordi; Sánchez-Valle, Raquel (Case Reports in Psychiatry, 2011)
We describe a case report of an 80-year-old woman who presented with symptomatology compatible with an episode of major depression with catatonia. After psychiatric admission, electroconvulsive therapy (ECT) was applied, but symptoms progressed with cognitive impairment, bradykinesia, widespread stiffness, postural tremor, and gait disturbance. After compatible magnetic resonance imaging (MRI), diffusion changes, and electroencephalogram (EEG) findings the case was reoriented to Creutzfeldt-Jakob disease (CJD). The genetic study found a methionine/valine heterozygosity at codon 129 of the prion protein gene PrPSc. On followup, a significant clinical recovery turned out. For this reason, EEG and MRI were repeated and confirmed the findings. The patient subsequently demonstrated progressive clinical deterioration and died 21 months later. The diagnosis was verified postmortem by neuropathology. The vCJD subtype MV2 is indeed characterized by early and prominent psychiatric symptoms and a prolonged disease duration however no frank clinical recovery has before been reported.